Methylchloroisothiazolinone/Methylisothiazolinone and Methylisothiazolinone Sensitivity in Hungary - Györgyi Pónyai; Ilona Németh; Erzsébet Temesvári (Dermatology Research and Practice)
Background. Due to allowing of methylisothiazolinone (MI) in cosmetics, cleaning products, and paints, an epidemic of MI-hypersensitivity emerged. Patch testing Kathon CG® (3:1 mixture of methylchloroisothiazolinone and methylisothiazolinone, MCI/MI) does not correctly detect MI contact allergy, due to the low concentration of MI in the test material. Methods. A retrospective survey was performed to estimate the prevalence of MCI/MI hypersensitivity in 14693 patients tested consecutively between 1993 and 2014. Moreover, currently 314 patients were prospectively tested with the allergens MCI/MI and with MI during one year. Results. MCI/MI hypersensitivity increased retrospectively from 0.5% to 6.0%. By current prospective testing we detected 25 patients (8%) with MCI/MI and/or MI positive reactions. Out of the 25 patients 10 were only MCI/MI positive, 9 were only MI positive, and 6 were MCI/MI and MI positive. If MI had not been tested separately, MI contact allergy would have missed in 36% of all detected cases and in 2.8% of the total 314 patients. Conclusions. The frequency of MCI/MI hypersensitivity is increasing also in Hungary. We confirm that, in order to detect MI contact allergy, it needs to be tested separately. A further increase of MI hypersensitivity might be expected in the future as products containing MI are still widely available.